(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Foam cup moulding of seamless and traceless undergarments is an important manufacturing technique for the intimate apparel industry. Nevertheless, there is limited knowledge about the optimization of the main moulding parameters. In this study, Response Surface Methodology (RSM), based on a Box-Behnken Design (BBD), was used to analyze the effects of the three main moulding factors (moulding temperature, dwell time and size of mould head) on the shape conformity of moulded bra cups and formulate a prediction model in a second-order polynomial form. Design and analysis of experimental data were carried out by the Minitab R15.1.30.0. The analyses revealed that moulding temperature greatly affected the shape conformity of moulded bra cup, and the interactions between moulding temperature and dwell time have major influence on the control of bra cup moulding process. The optimal cup shape conformity and the corresponding settings of the selected variables in bra cup moulding process were obtained by solving the quadratic regression model, as well as by analyzing the response surface contour plots. When moulding temperature and dwell time were set as 200° and 140s for a mould head size of 36C, the optimum shape conformity of the moulded bra cup was predicted as 83%. The adopted model was proved reasonably and effectively. This research provided a reference for the intimate apparel manufacturers to improve the control of the bra cup molding process and production efficiency.